2018
DOI: 10.1371/journal.pone.0192076
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 2015 earthquakes on a local hospital in Nepal: A prospective hospital-based study

Abstract: IntroductionNatural disasters pose a great challenge to the health systems and individual health facilities. In low-resource settings, disaster preparedness systems are often limited and not been well described. Two devastating earthquakes hit Nepal within a 17-days period in 2015. This study aims to describe the burden and distribution of emergency cases to a local hospital.MethodsThis is a prospective observational study of patients presenting to a local hospital for a period of 21 days following the earthqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 25 publications
2
46
1
Order By: Relevance
“…This is probably because such admissions were shortened to ensure all earthquake victims in need were admitted and appropriately treated. These findings are in line with a study in a rural hospital in Nepal describing the patient load in the three weeks after the earthquake, which found that earthquake-related conditions had significantly longer hospitalizations compared to other non-earthquake related admissions 17 .…”
Section: Discussionsupporting
confidence: 91%
“…This is probably because such admissions were shortened to ensure all earthquake victims in need were admitted and appropriately treated. These findings are in line with a study in a rural hospital in Nepal describing the patient load in the three weeks after the earthquake, which found that earthquake-related conditions had significantly longer hospitalizations compared to other non-earthquake related admissions 17 .…”
Section: Discussionsupporting
confidence: 91%
“…In a similar study by Thapa SS et al, 9 majority of population (61%) were in the age group 16-60 years. Likewise, in the prospective hospital based study by Giri S et al, 10 around 74% population were of the age group 15-65 years and in the earthquake disaster relief mission in Nepal by Singapore Armed Forces, 11 there were 77.9% adults.…”
Section: Discussionmentioning
confidence: 89%
“…To achieve these goals, we designed an interview questionnaire to be conducted in various localities (see Appendix 1). It includes the following question items: (1) Question items to grasp the impacts on people's lives, (2) Question items to grasp the degree of impact of the political on each industry in Nepal, (3) Question items to grasp the people's understanding of the political crisis. Then, according to responses from the local people, we identify the real problems of the situation in Nepal and the future problems.…”
Section: Objectivesmentioning
confidence: 99%
“…Landlocked between China and India, it is rich in animal and plant diversity and boasts of Mount Everest and the Himalayan mountain range. On May 12 th 2015, an earthquake with a magnitude of 7.8 occurred and killed nearly 9,000 people, injuring nearly 22,000 people [1], [2]. It made hundreds of thousands of Nepalese homeless with entire villages flattened across many districts of the country [3], [4], [5].…”
Section: Introductionmentioning
confidence: 99%